THE PLACE OF EXPEDIENT(MASLAHAT) IN THE LEADERSHIP OF THE ISLAMIC COMMUNITY - Torkashvand, Afsaneh; Kharanaghi, Mahmood Ghayyoum Zadeh; Heidari, Abbas Ali (International Journal of Research -GRANTHAALAYAH, 2018)
Expediency is one of the titles which have important statuses in the Islamic jurisprudence and its association with religious decrees is clarified while determining its concept and it specifies the authorities of the prudent leader. Expedient (Maslahat) in the view of Islam is defined as to do anything for the sake of material and spiritual benefit of the individual and society. Islamic religions do believe that Expedient (Maslahat) plays an essential role in the interpretation of the law, but there is some disagreement over its scope. Most jurisprudents consider expediency to be effective in divine rules when it is based on the expedients, and its purpose is to achieve expedients that can changed as according to the requirements of time and place. Examining and implementing this in the affairs of society is one of the duties that the Islamic ruler should observe. Therefore, it is necessary that the ruler considers the expedient in community management and use it as a key to solving problems and removing the obstacles. The present research project tries to examine the role of expedient in implementing the provincial leadership and seeks to answer the following questions: What is the relationship between the community leadership and the welfare state? How can the Islamic ruler utilize this rule? Another purpose is to explain this relationship as a solution and a key to solve the problems of the society including the conflict of the rules, which mainly deals with the jurisprudential texts in a qualitative way with an analytical attitude. Various research on leadership and expediency has been done separately, but it seems that the link between these two has not been mentioned yet. So, it seems necessary to carry out a new research on this issue to answer the questions raised in relation to these two categories.